Prototipe Kontrol Beban di Laboratorium Elektronika Polnep - Eko Mardianto; Taufik Muzakir (Vokasi, 2019)
In this study the author designed and realized the prototype of software using Android based on the Internet of Things that can control lighting, and air conditioner (AC) in the Electronic Laboratory room, especially the Robotics Laboratory. This device can be controlled remotely using Android. Raspberry PI besides serving as a controller can also be used as a server to connect to other devices. The use of remote control is used to anticipate the negligence of officers in turning off electricity in the Lab room when not in use anymore. To be able to control lighting and air conditioning which has a voltage of 220 V AC, while the output of raspberry pi is only 3.3 V DC for that it requires a relay driver circuit. This device is expected to later be developed in electronic engineering laboratories especially the Pontianak State Polytechnic electrical engineering department. The use of this application can help easy the controlling and monitoring of electricity in the electronics engineering robotics laboratory.